Ultrasensitive Determination of Human Chorionic Gonadotropin using a Molecularly Imprinted Electrochemical Sensor. Issue 22 (9th August 2017) - Shen, Xiaolei; Ma, Ya; Zeng, Qiang; Huang, Jianzhi; Tao, Jia; Wang, Lishi
Abstract: In this work, an ultrasensitive human chorionic gonadotropin (hCG) imprinted electrochemical sensor was constructed on the surface of a glassy carbon electrode (GCE) through surface imprinting. The imprinting template hCG was covalently bound onto the electrode which was modified by layer‐by‐layer coating of multi‐walled carbon nanotubes (MWCNTs), chitosan (CS) and glutaraldehyde (GA), Followed by electropolymerizing dopamine and effectively eluting, hCG imprinted polymer film was formed on the surface of the modified GCE. Benefiting from the application of MWCNTs and the imprinting effect, the designed sensor presented high sensitivity and selectivity with a widely linear detection range varying from 0.5 pg mL −1 to 250 ng mL −1 and a low detection limit of 0.035 pg mL −1 (S/N=3) which is superior to other electrochemical detection methods for hCG. Moreover, the imprinted sensor possessed low cross‐reactivity with multiple comparative proteins and high resistance to human serum effect. The results compared with enzyme‐linked immunosorbent assay (ELISA) further confirmed the accuracy and reliability of the hCG imprinted sensor. All electrochemical detection were performed in potassium hexacyanoferrate III (K3 [Fe(CN)6 ]) and potassium hexacyanoferrate II (K4 [Fe(CN)6 ]) trihydrate solution acting as a redox probe. Abstract : In this study, a highly sensitive and specific hCG/MIPs electrochemical sensor was successfully prepared by using covalent binding, electropolymerization and surface imprinting. This novel sensor is easily made and template saving which is particularly suitable for expensive and scarce biomacromolecules. Meanwhile, this designed sensor possessed wide linear range and low detection limit. Satisfying results of human serum analysis indicated that the proposed sensor would be a potential candidate for clinic diagnosis device versatilely suitable for diagnostically relevant proteins.